Perkembangan Lembaga Pendidikan Islam di Indonesia - Kholilur Rahman (Tarbiyatuna Kajian Pendidikan Islam, 2018)
This research was conducted to describe the history of Islamic educational institutions on the journey in the history of Indonesia through a long and tiring struggle. In the colonial era, various ways were done as a frontal effort from The Netherlands to stop the Islamic education that developed in some Islamic educational institutions which at that time was formed by pesantren and madrasah.Then on its development result to the dichotomy of educational institutions in Indonesia.Then on its development resulted in the dichotomy of educational institutions in Indonesia.This research uses literature method, which is a technique of collecting data through scientific literacy on the development of Islamic education institutions in Indonesia with the aim of revealing the travel side of Islamic institutions.So the results of this study can be useful to be a study of institutions of education.The result of this research is that many Netherlands colonial efforts to stop the educational process of Islamic education institutions under the pesantren and madrasah system.These efforts include the establishment of Priesnterraden, a strict supervision of educational processions in Islamic educational institutions; then published Teacher's Ordinance and Wild School Ordinance, as well as other efforts discussed in this study.